Elimination of P. berghei liver stages is independent of Fas (CD95/Apo-I) or perforin-mediated cytotoxicity - Renggli, J.; Hahne, M.; Matile, Hughe; Betschart, Bruno; Tschopp, J.; Corradin, Giampietro (My University, 1997)
Immunization of mammals with irradiated malaria sporozoites protects from a subsequent contact with the parasite. Protective immunity is directed against the pre-erythrocytic stages of the parasite, sporozoites and liver stages. Specific antibodies neutralize part of the infectious sporozoites injected by the mosquito vector, while liver stages are the target of a cellular immune response which is mediated by T cells. In this study, we evaluated the T-cell dependent protection induced by the injection of P. berghei irradiated sporozoites and the contribution of perforin and of the receptor/ligand system CD95/CD95L, two T cell-dependent mechanisms known to mediate elimination of target cells. Wild type, perforin deficient, CD95 mutant, CD95L mutant and perforin deficient/CD95L mutant mice were immunized with P. berghei irradiated sporozoites and submitted to a challenge with infectious sporozoites. All mice immunized with P. berghei irradiated sporozoites were protected against a sporozoite challenge, including perforin deficient/CD95L mutant animals. These results indicate that T cells do not kill malaria-infected hepatocytes via one of the known pathways, but rather that activated parasite-specific T cells produce cytokines which activate in cascade other mechanisms responsible for the intracellular elimination of the parasite.
Keywords: P.berghei; perforin; CD95/Apo-I; liver stage; CTL